(Electro)catalytic C-C bond formation reaction with a redox-active cobalt complex - van der Meer, Margarethe; Rechkemmer, Yvonne; Peremykin, Irina; Hohloch, Stephan; van Slageren, Joris; Sarkar, Biprajit (Chemical communications (Cambridge, England), 2014)
Cooperativity between cobalt and non-innocent ligands in electron transfer processes has been utilized for (electro)catalytic C-C bond formation reactions.Cooperativity between cobalt and non-innocent ligands in electron transfer processes has been utilized for (electro)catalytic C-C bond formation reactions.